Ressurreição e Acenos e Afagos: um estudo das masculinidades em Félix e João Imaculado. - Jimenez, Michele de Oliveira (2011)
Analyzing representations of masculinities in its relation to sexuality and gender, evidenced in the characters Félix, of the novel Ressurreição (1871/2005), by Machado de Assis, and João Imaculado, of the novel Acenos e afagos (2008), by João Gilberto Noll, this dissertation aims to understand, in these narratives, expressions of different representations of masculinity at the end of the 19th century and start of the 21st century. Accordingly, the comparative study of these narratives allows also to understand its links with the society, in different historical and cultural contexts, as it was intended to highlight here studying the meanings of the own name, the marriage, the family and the profession in the two novels.